Comparative Advantage and the Theory of Tariffs: A Multi-Country, Multi- Commodity Model - Jones, Ronald W. (Review of Economic Studies, 1961)
Journal Article Comparative Advantage and the Theory of Tariffs: A Multi-Country, Multi-Commodity Model Get access Ronald W. Jones Ronald W. Jones Rochester, N.Y. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 3, June 1961, Pages 161–175, https://doi.org/10.2307/2295945 Published: 01 June 1961